Black Objects in Supergravity Proceedings of the INFN-Laboratori Nazionali di Frascati School 2011 - Bellucci, Stefano (Springer Proceedings in Physics, 2013)
This is the sixth volume in a series of books on the general topics of supersymmetry, supergravity, black holes and the attractor mechanism. The present volume is based upon lectures held in May 2011 at the INFN-Laboratori Nazionali di Frascati School on Black Objects in Supergravity (BOSS2011), directed by Stefano Bellucci, with the participation of prestigious lecturers, including G. Lopes Cardoso, W. Chemissany, T. Ortin, J. Perz, O. Vaughan, D. Turton, L. Lusanna and S. Ferrara. All lectures were at a pedagogical, introductory level, a feature which is reflected in the specific "flavor" of this volume, which also benefited greatly from extensive discussions and related reworking of the various contributions.